High Infiltration of CD203c+ Mast Cells Reflects Immunosuppression and Hinders Prognostic Benefit in Stage II-III Colorectal Cancer - Li J; Mo Y; Wei Q; Chen J; Xu G (Dove Medical Press, 2023)
Jing Li,1,* Yuzhen Mo,2,* Qingqing Wei,1 Jian Chen,3 Guozeng Xu1 1Department of Oncology, Liuzhou People's Hospital of Guangxi Medical University, Liuzhou, Guangxi, People's Republic of China; 2Department of Radiation Oncology, Guangzhou Red Cross Hospital of Jinan University, Guangzhou, Guangdong, People's Republic of China; 3Department of Medical Oncology, Yantai Yuhuangding Hospital of Qingdao University, Yantai, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Guozeng Xu; Jian Chen, Email lzry19831002@yeah.net; chenjianyt@163.comBackground: Activated mast cells (AMCs) have been fully researched in inflammation and allergic reactions. However, the protumoral role of AMCs and their biomarker CD203c has not yet been investigated in colorectal cancer (CRC).Methods: We retrospectively collected 449 postoperative patients with stage II-III CRC at two different hospitals as the training (n=310) and validation (n=139) cohorts. These findings were further validated in the independent cohort (Integration of GSE39582 and GSE17536, n=489). The AMC density was assessed using CD203c staining or the CIBERSORT method. The main analysis was recurrence-free survival (RFS) and overall survival (OS).Results: As an independent factor, high AMC infiltration was associated with worse RFS/OS in the training (hazard ratio [HR]=3.437/3.014, all p< 0.001) and validation (HR=3.537/2.382, all p< 0.001) cohorts. We developed and validated an AMC-based nomogram for better stratification for postoperative recurrence in these two cohorts. The role of AMC density was further validated in the independent cohort. High AMC infiltration was associated with decreased RFS/OS after adjuvant chemotherapy (all p< 0.05). Approximately 74.2% of intramural CD203c+ AMCs expressed a high level of PD-L1. Multiple immunosuppressive pathways were enriched in high AMC infiltration tumors, including upregulation of the TNF-α/NF-κB and angiogenesis pathways and downregulation of the IFN-γ and IFN-α responses. AMC infiltration was reversely associated with CD8+ T-cell infiltration (all p< 0.05).Conclusion: High AMC infiltration is associated with worse survival outcomes in stages II-III CRC. AMC density may serve as a potential biomarker for survival benefit in patients receiving adjuvant chemotherapy. This AMC-based nomogram could provide better recurrence stratification. Immunosuppression in tumors with high AMC infiltration might contribute to promoting tumor progression.Keywords: CD203c, colorectal cancer, activated mast cell, immunosuppression, prognostic benefit